Pelatihan 3D Printing untuk Mengatasi Keterbatasan Media Pembelajaran Matematika bagi MGMP “Cosinus”: 3D Printing Training to Overcome the Limitations of Mathematics Learning Media for the “Cosinus” MGMP - Friantini, Rizki Nurhana; Winata, Rahmat; Novan, Christian; Anugrah, Siti Dian; Hidayat, Dina Damiyanti; Sugiharto, Sugiharto; Aziz, Mohammad Fahthul (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Interviews with mathematics teachers revealed issues related to the need for concrete, varied, and contextually relevant learning materials. The availability of concrete media remains limited in both quantity and utilization in mathematics instruction. Current technological developments offer opportunities for innovation in the creation of 3D learning media that can be viewed, interacted with, and manipulated by students. An innovative solution is the development of 3D mathematics learning media using 3D printing technology. Therefore, a community service program was implemented to address the identified problem through this innovation. The program consisted of training mathematics teachers in designing and producing 3D mathematics learning media using 3D printing. The partner involved in this activity was the Mathematics Teacher Working Group (MGMP) of Junior High School "Cosinus" in Palangka Raya City. The training aimed to provide knowledge on the design and production of 3D mathematics learning media through 3D printing technology. Conducted in two sessions, the training yielded satisfactory results, as evidenced by improvements in all observed aspects among participating mathematics teachers. Furthermore, it was concluded that 3D printing training for the development of mathematics learning media was effectively implemented.